Work competences of the heads of science department in the primary schools in Kuching district, Sarawak - Ngui, Felix Siong Hwa (Faculty of Computer Science and Information Technology, 2000)
The purpose of this study was to describe the level of competence of the heads of science department in the primary schools in the Kuching District.The whole population was chosen for the study. The survey method was adopted for the study. The questionnaire was self-developed and has an overall reliability score of 0.9410 on the Cronbach Alpha for reliability test.